2020
DOI: 10.1111/bjh.17071
|View full text |Cite
|
Sign up to set email alerts
|

Daratumumab monotherapy for relapsed/refractory multiple myeloma, focussed on clinical trial‐unfit patients and subsequent therapy

Abstract: Real-world outcomes of daratumumab monotherapy (DM) for relapsed/refractory multiple myeloma (RRMM) have remained unclear. We conducted a multicentre retrospective study of 107 patients receiving DM for RRMM. The cohort included 64 trial-unfit patients whose characteristics could not meet inclusion criteria in two previous clinical trials (GEN501 and SIR-IUS). The overall response rate (ORR), and median first and second progression-free survival (PFS1 and PFS2) and overall survival were 42Á1%, and 3Á6, 8Á1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
(59 reference statements)
2
15
1
Order By: Relevance
“…Other such studies have recently been published, almost exclusively in the relapse setting, and the number of patients included were most often less than 100 23‐27 (Atrash et al, 2021; Harvanová et al, 2021; Maouche et al, 2021; Szabo et al, 2021). Additionally, many of these studies focused on patients receiving dara monotherapy 24‐27 (Atrash et al, 2021; Maouche et al, 2021; Szabo et al, 2021) and demonstrated results similar to those for our DaraD/P cohort. Indeed, in similar populations, an ORR of 40%–50% could be achieved with a short median PFS of less than 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other such studies have recently been published, almost exclusively in the relapse setting, and the number of patients included were most often less than 100 23‐27 (Atrash et al, 2021; Harvanová et al, 2021; Maouche et al, 2021; Szabo et al, 2021). Additionally, many of these studies focused on patients receiving dara monotherapy 24‐27 (Atrash et al, 2021; Maouche et al, 2021; Szabo et al, 2021) and demonstrated results similar to those for our DaraD/P cohort. Indeed, in similar populations, an ORR of 40%–50% could be achieved with a short median PFS of less than 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…While clinical trials demonstrate impressive benefit of dara‐based therapies, possible discordance with real‐world practice might exist, as many patients in the real world are known to be ineligible for clinical trials 22,23 . A few small real‐world multicentre studies specifically focusing on dara have been published, confirming the promising activity noted in clinical trials 23‐27 (Atrash et al, 2021; Harvanová et al, 2021; Maouche et al, 2021; Szabo et al, 2021) 28‐31 . There remains a paucity of studies evaluating the outcomes of dara‐containing regimens in larger real‐world cohorts.…”
mentioning
confidence: 99%
“…Our previous study reported the favorable efficacy and infusion-related safety of 64 RRMM patients who would be unfit to participate in the GEN501 or SIRIUS due to comorbidities including an Eastern Cooperative Oncology Group Performance Status of ≥3, meningeal involvement, anemia of <75 g/L, neutropenia of <1.0×10 9 /L, thrombocytopenia <75×10 9 /L, and renal insufficiency with a glomerular filtration rate of <20 mL/min/1.73 m 2 . No reported IRRs interrupted the daratumumab schedule, and all IRRs were manageable with supportive care [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…To prevent IRRs, the patients received 100 mg of intravenous methylprednisolone at the first and second daratumumab infusions. Other supportive care and preventive medications were administered as described in our previous reports [ 8 ]. The clinical outcomes of the 3 patients are summarized in Table 2 .…”
Section: Casementioning
confidence: 99%
“…The treatment paradigm in MMis evolving with the introduction of various immunotherapies [ 2 ]. First came the monoclonal antibodies (mAbs), which represented a paradigm shift in treating all MM stages [ 3 , 4 , 5 , 6 , 7 ]. The initial mAbs included daratumumab, which targets CD38 on MM cells’ surface [ 8 , 9 ], and elotuzumab, which targets SLAMF7 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%